Design and characterization of microcapsules-integrated collagen matrixes as multifunctional three-dimensional scaffolds for soft tissue engineering. (September 2016) - del Mercato, Loretta L.; Passione, Laura Gioia; Izzo, Daniela; Rinaldi, Rosaria; Sannino, Alessandro; Gervaso, Francesca
Abstract: Three-dimensional (3D) porous scaffolds based on collagen are promising candidates for soft tissue engineering applications. The addition of stimuli-responsive carriers (nano- and microparticles) in the current approaches to tissue reconstruction and repair brings about novel challenges in the design and conception of carrier-integrated polymer scaffolds. In this study, a facile method was developed to functionalize 3D collagen porous scaffolds with biodegradable multilayer microcapsules. The effects of the capsule charge as well as the influence of the functionalization methods on the binding efficiency to the scaffolds were studied. It was found that the binding of cationic microcapsules was higher than that of anionic ones, and application of vacuum during scaffolds functionalization significantly hindered the attachment of the microcapsules to the collagen matrix. The physical properties of microcapsules-integrated scaffolds were compared to pristine scaffolds. The modified scaffolds showed swelling ratios, weight losses and mechanical properties similar to those of unmodified scaffolds. Finally, in vitro diffusional tests proved that the collagen scaffolds could stably retain the microcapsules over long incubation time in Tris–HCl buffer at 37 °C without undergoing morphological changes, thus confirming their suitability for tissue engineering applications. The obtained results indicate that by tuning the charge of the microcapsules and by varying the fabrication conditions, collagen scaffolds patterned with high or low number of microcapsules can be obtained, and that the microcapsules-integrated scaffolds fully retain their original physical properties. Graphical abstract: Highlights: 3D collagen scaffolds with charged microcapsules were developed by a facile method. Stimuli responsive biodegradable multilayer microcapsules were synthesized. Scaffolds with microcapsules showed mechanical properties similar to pristine scaffolds. Scaffolds could stably retain the microcapsules over long incubation time. Microcapsules-integrated scaffolds fully retain their original physical properties.